Effect and synergy of different exogenous additives on gel properties of the mixed shrimp surimi (Antarctic krill and white shrimp). (7th June 2022) - Zhang, Biao; Guo, Xuan; Lin, Junxin; Sun, Peizi; Ren, Xiang; Xu, Wei; Tong, Yi; Li, Dongmei
Summary: The object of this study was a high‐protein Antarctic krill ball which was made of mixed shrimp surimi (Antarctic krill and white shrimp). The effects of four different exogenous additives on gel properties and spatial structure of mixed shrimp surimi systems during processing were investigated by texture profile analysis, low‐field nuclear magnetic resonance, magnetic resonance imaging, Fourier‐transform infrared spectroscopy, scanning electron microscopy and rheology analysis, according to product formulation and processing conditions. Different exogenous additives improved distinctly the mixed shrimp surimi system. The use of the four exogenous additives combined had a synergistic promotional effect. Acetylated distarch adipate, egg white powder and soy protein isolate played a vital role in producing high‐protein Antarctic krill balls. The relatively limited improvement of transglutaminase could be attributed to processing temperature and the presence of autolytic enzymes originated intrinsically from Antarctic krill surimi. Abstract : This study explored the effects of four exogenous additives on gelation properties of mixed shrimp surimi.